Development of a fiber daylighting system based on a small scale linear Fresnel reflector: Theoretical elements. (15th February 2018) - Barbón, A.; Sánchez-Rodríguez, J.A.; Bayón, L.; Barbón, N.
Highlights: The design of a fiber daylighting system based on a linear Fresnel reflector. A daylighting system like this has not been studied in the literature so far. This work focuses on the design of a new reflector cavity. The cavity used in a conventional linear Fresnel reflector is not suitable for it. The work presented in this paper shows the luminous energy produced per month. Abstract: This paper describes the details of the design of a small scale linear Fresnel reflector ( SSLFR ) applied to a daylighting system based on optical fiber bundles ( OFBs ). This study shows the influence of the SSLFR design parameters (mirror width, mirror length, reflector cavity height, and number of mirrors) and the parameters of the optical fiber. A new reflector cavity is designed, consisting of two right trapeziums. Each trapezium collects the incident solar irradiance of the mirrors located at each side of the central mirror. The reflector cavity has two focal points, located in the middle of the aperture of each trapezium. A MATLAB code was developed in order to obtain the optical efficiency of the new reflector cavity and numerical simulations are presented. Two SSLFR configurations, C 1 and C 2, are studied. C 1 is the configuration used in large-scale LFRs and does not consider lateral movement of the OFBs, as is the case in configuration C 2 . Each of these configurations is analyzed considering the optimal length and longitudinal position of the OFB . Numerical simulations are presented for both configurations using the MATLAB environment. Power consumption based calculations are carried out using the lumen method and the potential electric energy saving is evaluated. The illumination levels obtained are then compared using the lighting design software DIAlux, a free software widely used as a planning tool by lighting designers. The results show a considerable electric energy saving with configuration C 2, although configuration C 1 also presents good energy savings.